2018
DOI: 10.1007/s10522-018-9758-4
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyltransferase inhibitor and rapamycin correct aberrant genome organisation and decrease DNA damage respectively, in Hutchinson–Gilford progeria syndrome fibroblasts

Abstract: Hutchinson–Gilford progeria syndrome (HGPS) is a rare and fatal premature ageing disease in children. HGPS is one of several progeroid syndromes caused by mutations in the LMNA gene encoding the nuclear structural proteins lamins A and C. In classic HGPS the mutation G608G leads to the formation of a toxic lamin A protein called progerin. During post-translational processing progerin remains farnesylated owing to the mutation interfering with a step whereby the farnesyl moiety is removed by the enzyme ZMPSTE24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 99 publications
3
35
0
1
Order By: Relevance
“…In this study, we demonstrate for the first time that chromosome 18 territories are found in the nuclear interior of normal proliferating control cells, the only change being that they have been immortalized by hTERT. This interior location is also observed in the two immortalized HGPS cell lines and corresponds to that previously observed nuclear position for chromosome 18 territories in HGPS cells . Another novel finding of this study is that chromosome X territories are located in the nuclear interior in the T08 HGPS cell line.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, we demonstrate for the first time that chromosome 18 territories are found in the nuclear interior of normal proliferating control cells, the only change being that they have been immortalized by hTERT. This interior location is also observed in the two immortalized HGPS cell lines and corresponds to that previously observed nuclear position for chromosome 18 territories in HGPS cells . Another novel finding of this study is that chromosome X territories are located in the nuclear interior in the T08 HGPS cell line.…”
Section: Discussionsupporting
confidence: 90%
“…This interior location is also observed in the two immortalized HGPS cell lines and corresponds to that previously observed nuclear position for chromosome 18 territories in HGPS cells. 40,66,71 Another novel finding of this study is that chromosome X territories are located in the nuclear interior in the T08 HGPS cell line. This line does not contain the classical G608G lamin A mutation and so does not express progerin, and displays lamin A expression (Supporting Information Figure S6).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Rogers et al (2018) discuss the role of circadian clocks in adult stem cell maintenance and how they control stem cell function. The topic of therapeutics is continued by Bikkul's article which focuses on a rare premature ageing disease: Hutchinson-Gilford Progeria Syndrome (HGPS) and drug treatments and regimes currently used in clinical trials (Bikkul et al 2018). Finally, the review by Ezcurra (2018) discusses a new exciting research area in the field of ageing: how the human microbiome can change in specific disease states.…”
mentioning
confidence: 99%